2021
DOI: 10.2174/1573396317666210426102610
|View full text |Cite
|
Sign up to set email alerts
|

New Strategies for Necrotizing Enterocolitis Diagnosis and Prevention in Newborns

Abstract: : Necrotizing enterocolitis is one of the most frequent and severe gastrointestinal diseases that affect preterm newborns in Neonatal Intensive Care Units. It was firstly described in 1960s, but this clinical entity was not widely recognized until the advent of modern neonatal intensive care. The disease is characterized by submucosal edema, infiltration of intestinal wall by immune cells, specifically neutrophils and, in severe forms, wall necrosis that leads to intestinal perforation. Its incidence is invers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 76 publications
0
5
0
Order By: Relevance
“…CRP levels rise sharply in response to infection and trauma, and whole-blood CRP levels are widely used to assess various types of inflammatory responses. Studies ( 9 , 10 ) have shown that PCT, CRP, and IL-6 levels in patients with stage III NEC are significantly higher than those in patients with stage I–II and thus may serve as a benchmark for choosing a surgical option for NEC.…”
Section: Introductionmentioning
confidence: 99%
“…CRP levels rise sharply in response to infection and trauma, and whole-blood CRP levels are widely used to assess various types of inflammatory responses. Studies ( 9 , 10 ) have shown that PCT, CRP, and IL-6 levels in patients with stage III NEC are significantly higher than those in patients with stage I–II and thus may serve as a benchmark for choosing a surgical option for NEC.…”
Section: Introductionmentioning
confidence: 99%
“…It primarily affects the ileum, jejunum, and/or colon, making it a significant condition [2] . It is characterized by submucosal edema, infiltration of immune cells (especially neutrophils) in the intestinal wall, and intestinal perforation due to necrosis of the intestinal wall in severe cases [3] . The pathogenesis of NEC is not fully understood.…”
Section: Introductionmentioning
confidence: 99%
“…Ischemic factors, feeding with hyperosmolar mixtures, malabsorption, forced amounts of food, and bacterial flora lead to the damage of the intestinal mucosa [4,5]. In NEC, in almost all cases, there are factors of social, medical-organizational, and medical-biological nature, which are either a cause or an aggravating situation for the occurrence of NEC and fatalities [3,6]. In connection with the abovementioned, the task was set to prove the significance of the combinations of these factors for a reliable study of the incidence rate.…”
Section: Introductionmentioning
confidence: 99%
“…Other researchers consider hypotension during the week of life as an independent risk factor for the development of NEC, as circulatory disorders during this period of life can lead to impaired gastrointestinal blood flow, and, consequently, to a high incidence of necrosis [6,8,9].…”
Section: Introductionmentioning
confidence: 99%